Approved drugs successfully repurposed against Leishmania based on machine learning predictions - Rafeh Oualha; Yosser Zina Abdelkrim; Ikram Guizani; Emna Harigua-Souiai (Frontiers in Cellular and Infection Microbiology, 2024)
Drug repurposing is a promising approach towards the discovery of novel treatments against Neglected Tropical Diseases, such as Leishmaniases, presenting the advantage of reducing both costs and duration of the drug discovery process. In previous work, our group developed a Machine Learning pipeline for the repurposing of FDA-approved drugs against Leishmania parasites. The present study is focused on an in vitro validation of this approach by assessing the antileishmanial effects of 10 predicted drug candidates. First, we evaluated the drugs’ activity against promastigotes from two strains of L. infantum and one of L. major, which caused distinct clinical manifestations, using an MTT assay. The standard anti-Leishmania drug Amphotericin B was used as a positive control. Five molecules demonstrated anti-Leishmania effects, out of which Acebutolol, Prilocaine and Phenylephrine are described herein for the first time. When tested on promastigote growth, Acebutolol displayed IC50 values ranging from 69.28 to 145.53 µg/mL. Prilocaine exhibited IC50 values between 33.10 and 45.81 µg/mL. Phenylephrine, on the other hand, presented IC50 values >200 µg/mL. The two remaining drugs, Dibucaine and Domperidone, exhibited significantly low IC50 values varying between 0.58 and 1.05 µg/mL, and 6.30 and 8.17 µg/mL, respectively. Both compounds were previously described as anti-Leishmania agents in vivo. All five compounds demonstrated no notable cytotoxic effects on THP-1-derived macrophages at the IC50 concentrations, allowing for their testing on the intracellular form of L. major and L. infantum parasites. Interestingly, all compounds exhibited antileishmanial activity on amastigotes with enhanced IC50 values compared to the corresponding promastigotes. Noticeably, Dibucaine and Domperidone displayed IC50 values of at most 1.99 µg/mL. Acebutolol, Prilocaine and Phenylephrine showed IC50 values ranging from 13.84 to 66.81 µg/mL. Our previously published Computer-Aided repositioning pipelines of FDA-approved drugs as antileishmanial agents identified Dibucaine and Domperidone as candidates in support of previous in vivo studies. This study consolidates such findings through the in vitro validation against 2 Leishmania species, highly prevalent in Africa and Middle East, and reveals Acebutolol, Prilocaine, and Phenylephrine as novel anti-Leishmania effectors, confirming the relevance of our approach and calling for further investigations.